14 The effect of different contouring techniques on cardiac magnetic resonance assessment of right ventricular volumes in repaired tetralogy of fallot: implications on preoperative thresholds for intervention. (17th July 2020) - Lodge, Freya; McAloon, Christopher; Steeds, Rick; Moody, William; Hudsmith, Lucy
Abstract : Introduction: Patients with repaired tetralogy of Fallot (RTOF) develop chronic pulmonary regurgitation and require monitoring for right ventricular dilatation. Pulmonary valve replacement can prevent irreversible right ventricular (RV) dilatation and dysfunction and cardiac magnetic resonance (CMR) is used to facilitate its optimal timing. There are however, different techniques published for measuring RV volumes. We sought to determine whether the choice of myocardial contouring technique affects preoperative RV volumetric thresholds for intervention. Methods: Consecutive patients (n = 24, age 25.2±15.5 years, 42% male) with RTOF were identified retrospectively, having undergone CMR for clinical surveillance at a Level 1 ACHD surgical referral centre. Volumetric analysis was made by two experienced, independent observers blinded to clinical status. Right ventricular volumes were measured using three contouring techniques: 1) smooth, where the trabeculae were counted as part of the blood volume; 2) detailed, using semi-automated thresholding; 3) detailed, with manual contours. For 2) and 3), trabeculae and sub-valvar apparatus were counted as part of the myocardium. Inter-observer variability (F.L. & C.M.) was assessed blinded in 5 randomly selected patients. Results: Right ventricular end-diastolic volume (EDV) was largest for smooth contours compared with thresholding and manual (table ), as was end-systolic volume (ESV) (p<0.001 for all comparisons). Ejection fraction was similar for smooth and thresholding (p=0.96) but was larger for manual (p=0.005). In four cases, the indexed EDV was ≥130ml/m 2 by smooth contouring, but <130ml/m 2 for both detailed techniques. There was excellent inter-observer agreement for the smooth method (ICC: EDV 1.0 (confidence interval 0.98-1.0, p<0.001); ESV 0.94 (0.55-0.99, p=0.001) and detailed thresholding (EDV 0.94 (0.52-0.99, p=0.04); ESV 0.96 (0.65-1.0, p=0.02) with the weakest agreement seen for the detailed manual method (EDV 0.89 (0.33-0.99, p=0.01); ESV 0.88 (0.30-0.99, p=0.01). Conclusions: Smooth right ventricular contouring in RTOF creates larger RV volumes than detailed and may result in differences in management strategy. Smooth contouring is more reproducible than detailed methods using thresholding. Manual contouring was the least reproducible in this series. Our results are similar to studies of left ventricular contouring demonstrating larger volumes using smooth compared with detailed methods. The difference in right ventricular volume is accentuated in RTOF due to increased RV trabeculation. Consensus on contouring techniques in RTOF is vital to ensure standardisation of care. Conflict of Interest: None